The affinity bridge : a Newbury & Hobbes investigation - Mann, George (Tor, 2009)
Sir Maurice Newbury and Miss Veronica Hobbes, agents of Queen Victoria, battle both physical and supernatural enemies of the crown. They are called in to investigate the wreckage of a crashed airship and its missing automaton pilot while dealing with a zombie plague in the slums of the capital and attempting to solve a string of strangulations credited to a mysterious glowing policeman.